Use of the Strength of Recommendation Taxonomy (SORT) to assess full-mouth treatments of chronic periodontitis - Canabarro, Antonio; Marcantonio, Elcio [UNESP]; De-Deus, Gustavo (Nihon Univ, School Dentistry, 2015)
Previous studies have not resolved whether scaling and root planing with a full-mouth (with or without antiseptics) or quadrant approach is better for treatment of chronic periodontitis. We identified relevant studies and used Strength of Recommendation Taxonomy (SORT) criteria to critically interpret the results of all relevant studies. A literature search was performed using the PubMed, EMBASE, and Cochrane databases up to July 2015. Selected studies were stratified according to their quality, quantity, and consistency. In total, 377 studies were identified, and 36 articles selected for retrieval were stratified according SORT criteria, as follows: no level 1 studies, 15 level 2 studies, and 21 level 3 studies (which were excluded from subsequent analysis). Among the selected level 2 studies, including seven randomized clinical trials and three systematic reviews, 67% showed no significant difference between scaling and root planing with a full-mouth or quadrant approach. In conclusion, on the basis of the best available data, the strength of evidence is grade B (consistent, low-quality evidence) for full-mouth (with or without antiseptics) and quadrant scaling and root planing for treatment of chronic periodontitis.
Keywords: full-mouth disinfection; full-mouth scaling; scaling and root planing; SORT